Negotiating the Maximum-Security Offender Identity: Experiences From Incarcerated Women. (May 2020) - Qhogwana, Sibulelo
The representation of women classified as maximum-security offenders continues to be a challenge due to paucity of research regarding their experiences. Generally, their stories are masked under the experiences of the other categories of incarcerated women. Drawing from a larger study conducted with incarcerated women in a South African correctional centre in Johannesburg, in this article I provide a thematic analysis of in-depth interviews on the lived experiences of negotiating the maximum-security offender identity by 13 women. The results suggest that the maximum-security offender identity is associated with rejection, dehumanisation, denial of agency, restricted movement, and labelling. The article also highlights the significance of providing agency to incarcerated women in deconstructing stereotypes that represent them as angry and uneducated with no value to society. A more balanced repositioning of their stories emerges as they get an opportunity to construct their own experiences.